Effect on falls of providing single lens distance vision glasses to multifocal glasses wearers: VISIBLE randomised controlled trial. (25th May 2010) - Haran, Mark J; Cameron, Ian D; Ivers, Rebecca Q; Simpson, Judy M; Lee, Bonsan B; Tanzer, Michael; Porwal, Mamta; Kwan, Marcella M S; Severino, Connie; Lord, Stephen R
Abstract : Objective To determine whether the provision of single lens distance glasses to older wearers of multifocal glasses reduces falls. Design Parallel randomised controlled trial stratified by recruitment site and source of referral, with 13 months' follow-up and outcome assessors blinded to group allocation. Setting Community recruitment and treatment room assessments in Sydney and Illawarra regions of NSW, Australia. Participants 606 regular wearers of multifocal glasses (mean age 80 (SD 7) years). Inclusion criteria included increased risk of falls (fall in previous year or timed up and go test >15 seconds) and outdoor use of multifocal glasses at least three times a week. Interventions Provision of single lens distance glasses with recommendations for wearing them for walking and outdoor activities compared with usual care. Main outcome measures Number of falls and injuries resulting from falls during follow-up. Results Single lens glasses were provided to 275 (90%) of the 305 intervention group participants within two months; 162 (54%) of the intervention group reported satisfactory use of distance glasses for walking and outdoor activities for at least 7/12 months after dispensing. In the 299 intervention and 298 control participants available to follow-up, the intervention resulted in an 8% reduction in falls (incidence rate ratio 0.92, 95% confidence interval 0.73 to 1.16). Pre-planned sub-group analyses showed that the intervention was effective in significantly reducing all falls (incidence rate ratio 0.60, 0.42 to 0.87), outside falls, and injurious falls in people who regularly took part in outside activities. A significant increase in outside falls occurred in people in the intervention group who took part in little outside activity. Conclusions With appropriate counselling, provision of single lens glasses for older wearers of multifocal glasses who take part in regular outdoor activities is an effective falls prevention strategy. The intervention may be harmful, however, in multifocal glasses wearers with low levels of outdoor activity. Trial registration Clinical trials NCT00350855 .